ANDROGEN DEPRIVATION THERAPY USING OSATERONE ACETATE IN DOGS WITH BENIGN PROSTATIC HYPERPLASIA - DHIVYA, T R; SRIDEVI, P; KULASEKAR, K; KUMARASAMY, P (The Indian Journal of Animal Reproduction, 2016)
Benign Prostatic Hyperplasia (BPH) positive dogs were randomly treated with Osaterone acetate (OSA, n=10, 7 days, p.o.), and 6 BPH positive dogs served as untreated controls. Following treatment, the time taken for the remission of clinical signs ranged from 2-30 days with significant reduction in prostatic volume from month 2 to month 6 of the treatment. No adverse effects were noticed following OSA administration and all the treated dogs experienced complete clinical remission and stayed in remission throughout the 6 month trial period. This indicated that OSA rapidly and markedly reduced prostatic volume in dogs with BPH.